Safety Huddle methodology development in patient safety software: an experience report - Lucas Rodrigo Garcia de Mello; Barbara Pompeu Christovam; Ana Paula Amorim Moreira; Erica Brandão de Moraes
ABSTRACT Objectives: to report the development and implementation of a digital tool developed by a group of nurses and information technology professionals working in healthcare quality management. Methods: an experience report regarding the development of the Safety Huddle digital model, using the agile Scrum methodology. Results: the first stage was the development of the model proposed by the team of nurses and IT professionals, based on the demand of quality and patient safety leaders in Brazil, and the second phase was the software implementation. Final Considerations: the development and implementation of the Safety Huddle contributed to expedite the detection and distribution of actions, in addition to promoting integration among teams, accountability, and empowerment of professionals to foresee and identify issues related to patient safety and face them through action plans.